Quality of Fisheries Investment License Services in Donggala District Investment & PTSP - Ade Irma (Publik : (Jurnal Ilmu Administrasi), 2021)
Various stories experience the community complained about the services that have been provided by the Door Integrated Investment and Licensing Office (DPMPTSP) of Donggala regency of Central Sulawesi ProvinceFor a long time the community complained about the implementation of license services that felt very far from his expectations. The purpose of this study was to determine the quality of service for fishery sector investment permits at the Investment Office & PTSP, Donggala Regency, Central Sulawesi Province. The research method uses a qualitative descriptive approach. Determination of informants is done purposively. Collecting data using observation, and interviews. The results of this study use 5 dimensions in service quality, namely: (1) Tangibles (Physical Evidence), the results of research in this dimension indicate that the physical evidence in public services is still inadequate in terms of facilities and infrastructure. which exists. (2) Reliability, the results of research in this dimension are quite good, judging from the HR owned by the office. (3) Responsiveness, the results of this dimension study indicate the lack of responsiveness possessed by employees in the office. (4) Assurance, the results of this study indicate that the ability or friendliness of the employees in the office is good in increasing community satisfaction. (5) Empathy, these results show that the dimension of empathy in service quality is very necessary so that the people who carry out the management of the office feel appreciated.